Epoxy/fish scales hydroxyapatite (FsHAp) composites toughened by liquid natural rubber for biomedical applications - Arkan, Algarahi Alhussein (Tanjong Malim, 2019)
Epoxy/fish scales hydroxyapatite (FsHAp) composites toughened by liquid natural rubber for biomedical applications by Arkan, Algarahi Alhussein